2020
DOI: 10.1088/1538-3873/ab3e18
|View full text |Cite
|
Sign up to set email alerts
|

Systematics in the ALMA Proposal Review Rankings

Abstract: The results from the ALMA proposal peer review process in Cycles 0-6 are analyzed to identify any systematics in the scientific rankings that may signify bias. Proposal rankings are analyzed with respect to the experience level of a Principal Investigator (PI) in submitting ALMA proposals, regional affiliation (Chile, East Asia, Europe, North America, or Other), and gender. The analysis was conducted for both the Stage 1 rankings, which are based on the preliminary scores from the reviewers, and the Stage 2 ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…This was first discovered in HST observing proposals where male PIs had better success rates than female PIs (Reid 2014). Similar trends have been found at ESO (Patat 2016), ALMA (Lonsdale et al 2016;Carpenter 2020), NRAO (Lonsdale et al 2016), and the Canada-France-Hawaii Telescope (CFHT) and Gemini Observatory (Spekkens et al 2018).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…This was first discovered in HST observing proposals where male PIs had better success rates than female PIs (Reid 2014). Similar trends have been found at ESO (Patat 2016), ALMA (Lonsdale et al 2016;Carpenter 2020), NRAO (Lonsdale et al 2016), and the Canada-France-Hawaii Telescope (CFHT) and Gemini Observatory (Spekkens et al 2018).…”
Section: Resultssupporting
confidence: 67%
“…Other effects such as prestige bias complicate the interpretation of the data. For example, some studies have noted a dependence on the gender-based success rate and PI seniority (Spekkens et al 2018); the seniority of the review panels (Patat 2016); and the potential privilege of a proposer being a member of the TAC (Greaves 2018)-although Carpenter (2020) did not find any correlation. Numerous studies have noted that both males and females evaluate work by males higher than females for similar results.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this paper, we update the analysis presented in Carpenter (2020) and investigate any changes in the systematics in the past two ALMA cycles (Cycle 7 and Cycle 8). Section 2 provides an overview of the ALMA proposal review process.…”
Section: Introductionmentioning
confidence: 99%
“…Vera Rubin, that access to Mount Wilson observatory for women was a struggle [4]. Recent empirical studies have shown that gender biases in the attribution of telescope time persist at major facilities such as the Atacama Millimeter Array [5], the Hubble Space Telescope [6], the European Southern Observatory [7], and the NRAO [8]. Although women are now better represented in large scientific collaborations in astronomy, only few of them serve as leaders in these teams [9], and when it gets to receiving a share of a prize, they can be forgotten [10].…”
Section: Introductionmentioning
confidence: 99%